Strategic map of management of the institutional development plan 2015-2019 of the Federal University of Espírito Santo: a scenario and target analysis (Research, Society and Development, 2020)
The Institutional Development Plan (PDI) and the Management Report are institutional documents, mandatory to assist university management in their planning. Considering that the Federal University of Espirito Santo (UFES) will propose a new PDI the objective of this article was to compare the goals set for the management area in the period from 2015 to 2019 and to verify if they were achieved. It can be seen that the analysis of the reports is insufficient. In a complementary way, a SWOT analysis was carried out from the point of view of the managers of the São Mateus Campus who emphasized that the institution has a greater number of threats and negative points than opportunities and strengths. This fact is corroborated by the situational analysis carried out.